2021
DOI: 10.3389/fnut.2021.763700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation With Clostridium butyricum on the Amelioration of Growth Performance, Rumen Fermentation, and Rumen Microbiota of Holstein Heifers

Abstract: In China, the use of antibiotics growth promoters as feed additives has been banned. The goal of raising dairy heifers is to gain a relatively high body weight on a high-fiber diet at first mating or calving, thus increasing economic benefits. The objective of this experiment was to explore the effects of supplemental Clostridium butyricum (C. butyricum) on growth performance, rumen fermentation and microbiota, and blood parameters in Holstein heifers. Twenty Holstein heifers [mean ± standard deviation (SD); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Whereas, in the study of Cai et al ( 2021 ), both total VFA concentration and VFA profiles were increased by supplementing C. butyricum at 0.05% and 0.10% of the basal diet; the increased VFA concentration was due to increased in vitro rumen DMD. It is reported that as a butyrate producer, C. butyricum could produce short-chain fatty acids and nutritional factors such as enzymes (exo-pectate lyase, pectin methylesterase, and endo-pectate lyase) and vitamins (vitamins B and E), which would favor the activities of both cellulolytic and amylolytic bacteria, thereby improving rumen fermentability (Araki et al, 2002 ; Li et al, 2021 ). This may explain the trend of a greater molar proportion of acetate with supplemented C. butyricum at a low dose (0.5 × 10 6 CFU/bottle) than control at high media pH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas, in the study of Cai et al ( 2021 ), both total VFA concentration and VFA profiles were increased by supplementing C. butyricum at 0.05% and 0.10% of the basal diet; the increased VFA concentration was due to increased in vitro rumen DMD. It is reported that as a butyrate producer, C. butyricum could produce short-chain fatty acids and nutritional factors such as enzymes (exo-pectate lyase, pectin methylesterase, and endo-pectate lyase) and vitamins (vitamins B and E), which would favor the activities of both cellulolytic and amylolytic bacteria, thereby improving rumen fermentability (Araki et al, 2002 ; Li et al, 2021 ). This may explain the trend of a greater molar proportion of acetate with supplemented C. butyricum at a low dose (0.5 × 10 6 CFU/bottle) than control at high media pH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ratio of Firmicutes to Bacteroidetes indicates the proportion of different VFA profiles in rumen such as propionate produced by Bacteroidetes (Paoli et al, 2019 ), which is consistent with the higher A:P ratio at media pH 6.6 than pH 6.0. Previous studies have demonstrated that C. butyricum could modulate the microbiota in the intestine of broiler chickens (Molnar et al, 2020 ), feces of weaned piglets (Zhang et al, 2018 ), or rumen of heifers (Li et al, 2021 ). Auffret et al ( 2017 ) reported that a high ratio of Proteobacteria to ( Firmicutes + Bacteroidetes ) was a good indicator for rumen dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, although the proportion of propionate quadratically changed after increasing the supplemented CB at both media pH levels, its differences among treatments were minimal from a biological perspective. Li et al (2021) in vivo) used in each study. Heat-stressed animals often decrease feed intake, which may positively affect fibre digestibility (i.e., an increase of acetate concentration) due to potentially longer rumen retention.…”
Section: Gas Production Dmd and Fermentation Characteristicsmentioning
confidence: 99%